Reviews. Issue 2 (1st July 2016) - Duffy, Peter
Why Theatre Matters: Urban Youth, Engagement and A Pedagogy of The Real by Kathleen Gallagher (2014) University of Toronto Press, Toronto, ISBN 9 7814 4262 6942, US29.95.